Liquefaction Potential Analysis Using Various Methods (Case Study of Railway Bridge in Sintuk Toboh Gadang District, Padang Pariaman Regency, West Sumatera) - Didi Yoriadi; Andriani Andriani; Abdul Hakam (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
The earthquake that rocked West Sumatra with a magnitude of 7.9 SR, a depth of 71 km, and an epicenter of 0.84 LS - 99.65 BT around 57 km Southwest of Pariaman on 30 September 2009 has caused damage to infrastructure and buildings and caused 383 fatalities. One of the problems caused by the earthquake is the liquefaction phenomenon. Liquefaction was reported to have occurred in Padang in the form of sand ejection coming out of cracks in the ground after the 7.9 SR earthquake in 2009. This study aims to determine the liquefaction potential of the Sintuk Toboh Gadang railway, Pariaman, using various liquefaction potential analysis methods so that the most practical and convincing method is obtained among these methods. In this study, the methods used to predict liquefaction are the Tsuchida (1970), Seed & Idriss (1971), Shibata & Teparaksa (1988), and Hakam (2020) methods. Field testing was conducted at four CPT test points, four NSPT test points, and machine drilling tests. The results showed that using the Tsuchida (1970) method, soil deposits at the four points tended to have liquefaction potential. The Seed & Idriss (1971) method showed that points 3, with depths of 8m and 14m, and point 4, with a depth of 8m, had liquefaction potential, while the Shibata & Teparaksa (1988) method using CPT data showed that at depths <10 meters there was a tendency for liquefaction to occur at the four points reviewed. The study's results using the Hakam (2020) method resemble the method proposed by Seed & Idriss (1971). It can be concluded that among the four methods, the most practical and convincing method is the Hakam (2020) method.